Low precipitation EPE packaging film and preparation method thereof
By using modified POE particles and high -stick silicane contraction compounds in the EPE glue film, combined with the effect of nano -nanoxide, the problem of migration of the inter -agent of the EPE rubber membrane layer is solved, and stability.
Patent Information
- Application Number
- CN202310738571.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-06-21
AI Technical Summary
The problem of additive migration between EPE film layers leads to the cross-linking degree of the intermediate POE layer not meeting the standard, resulting in the rapid aging rate of the adhesive film and the stratification of EVA and POE layers.
The modified POE particles and high -stick silicone contraction compounds are used to limit the migration of the aids through the common effect of nano -silicon oxide and silicide compounds to improve the quality and performance of the glue film.
The migration and analysis of the auxiliary in the EPE film has been greatly reduced, the cross -linking and stability of the glue membrane is improved, and the layered problems are avoided.
Smart Images

Figure CN116656264B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging adhesive films, and in particular relates to a low-precipitation EPE packaging adhesive film and a preparation method thereof. Background Art
[0002] Photovoltaic encapsulation film is one of the important materials in the photovoltaic industry. It plays the role of bonding solar cells to glass and backplanes. It also has multiple functions of mechanical buffering, encapsulation protection, and anti-ultraviolet protection for photovoltaic modules. Photovoltaic encapsulation film is one of the key materials that affect the service life and power generation of photovoltaic modules. The technical research and development and upgrading of photovoltaic encapsulation film have a driving significance for the development of the photovoltaic industry.
[0003] After years of development, photovoltaic encapsulation films have gradually formed EVA films made of ethylene-vinyl acetate copolymer (EVA) as the basic material; and POE films made of ethylene-octene copolymer (POE) as the basic material. The chemical structure of vinyl acetate is polar, and its electrons can migrate under voltage conditions. Photovoltaic modules using EVA films will experience PID effect during the power generation process, which will lead to a significant decrease in the power generation of photovoltaic modules, especially in modules using P-type Perc and N-type Topcon double-sided cells. The PID problem is more serious. There are also some problems in using POE films to prepare photovoltaic modules. Among them, there are fewer sources of POE raw materials. At the same time, due to the polarity of POE itself, the adhesion of POE films to cells, glass and backplanes is relatively low compared to EVA. In addition, POE films are prone to problems such as bubbles, paralleling and slipping during the lamination process of photovoltaic modules, which will lead to a decrease in the packaging yield of photovoltaic modules.
[0004] In order to deal with the above problems, a new type of composite film (EPE) has gradually developed in the industry. The film is prepared by three-layer co-extrusion with POE as the middle layer and EVA as the outer layers on both sides. This kind of film has well solved the adhesion problem of POE film and the PID effect problem of EVA film, and can reduce costs and increase efficiency to a certain extent. However, due to the large polarity difference between EVA and POE, EPE film also has some unresolved problems. Among them, the most common one is the problem of additive migration. When this phenomenon occurs, it is easy to cause the cross-linking degree of the middle POE layer to fail to meet the standard, resulting in the aging of the film in the later stage too fast, and the stratification problem between the EVA film layer and the POE film layer. Summary of the invention
[0005] The invention provides a low-precipitation EPE encapsulation adhesive film and a preparation method thereof, so as to solve the problem of auxiliary agent migration between EPE adhesive film layers.
[0006] In order to solve the above technical problems, the present invention provides a preparation method of a low-precipitation EPE encapsulation film, comprising: mixing and configuring the raw materials of each layer according to a formula, and forming a three-layer structure through melt co-extrusion; the three-layer structure is a POE layer in the inner layer and an EVA layer in the outer layer; wherein the raw materials selected for the POE layer are modified POE particles; the preparation method of the modified POE particles comprises the following steps: firstly mixing nano silicon dioxide, an antioxidant, a light stabilizer, a cross-linking agent, an auxiliary cross-linking agent and a siloxane condensate evenly, then mixing them with POE particles, and then melting, extruding and granulating to obtain the modified POE particles for standby use; the preparation method of the siloxane condensate comprises the following steps: adding a catalyst to a silane coupling agent and a silicate in a mixed solution of alcohol and water for hydrolysis and condensation, and rotary evaporating to obtain the siloxane condensate; the raw materials selected for the EVA layer include EVA particles, an antioxidant, a light stabilizer, a cross-linking agent, an auxiliary cross-linking agent and a silane coupling agent.
[0007] In another aspect, the present invention further provides a low-precipitation EPE packaging film obtained by the preparation method as described above, comprising a siloxane condensate and nano-silicon dioxide.
[0008] The beneficial effects of the present invention are that the low precipitation EPE encapsulation film and the preparation method thereof adopt the method of hydrolysis and condensation of silane coupling agent and silicate to form an amorphous and highly viscous siloxane condensate, the obtained siloxane condensate retains the silicon-oxygen bond and functional group to maintain the original function of the silane coupling agent, and at the same time, the high viscosity and large molecular weight make it difficult to move and easier to adhere to the surface of particles; the surface of nano-silicon dioxide has certain polar groups, which is easier to combine with polar additives and play the role of fixing the additives. Through the joint action of the siloxane condensate and the nano-silicon dioxide, the migration and precipitation amount of the additives in the EPE film is greatly reduced, and the quality and performance of the EPE film are effectively improved.
[0009] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practicing the present invention.
[0010] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0012] Figure 1 It is a schematic diagram of the process of preparing siloxane condensate by hydrolysis condensation reaction of silane coupling agent and silicate of the present invention;
[0013] Figure 2 is a Raman spectrum of the siloxane condensate of the present invention;
[0014] Figure 3 It is a TEM image of the nano-silicon dioxide and the nano-silicon dioxide mixture of the present invention;
[0015] Figure 4 It is a SEM picture of the layer made from the pure POE particles and the modified POE particles of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The invention provides a method for preparing a low-precipitation EPE packaging film, comprising: mixing and configuring raw materials of each layer according to a formula, and forming a three-layer structure through melt co-extrusion; the three-layer structure comprises a POE layer in an inner layer and an EVA layer in an outer layer; wherein the raw materials selected for the POE layer are modified POE particles; the method for preparing the modified POE particles comprises the following steps: firstly uniformly mixing nano silicon dioxide, an antioxidant, a light stabilizer, a crosslinking agent, an auxiliary crosslinking agent and a siloxane condensate, then mixing them with the POE particles, and then melting, extruding and granulating to obtain the modified POE particles for standby use; the method for preparing the siloxane condensate comprises the following steps: adding a catalyst to a silane coupling agent and a silicate in a mixed solution of alcohol and water for hydrolysis and condensation, and rotary evaporating to obtain the siloxane condensate; the raw materials selected for the EVA layer comprise EVA particles, an antioxidant, a light stabilizer, a crosslinking agent, an auxiliary crosslinking agent and a silane coupling agent.
[0018] like Figure 1 As shown, KH570 and tetraethyl orthosilicate are used as examples to carry out hydrolysis and condensation reaction of silane coupling agent and silicate to prepare siloxane condensate.
[0019] In this embodiment, specifically, the silane coupling agent is any one of KH550, KH560, KH570, KH792, OFS-6341, KBM403, KBM4803, KM5803 and DL602, or a combination of at least two thereof, preferably a combination of KH550 and KH570, a combination of KH570 and KH792, a combination of KH570 and KBM403, a combination of KH570 and OFS-6341, a combination of KH570 and KBN4803, a combination of KH570 and KM5803, or a combination of KH570 and DL602.
[0020] In this embodiment, specifically, the silicate is any one of tetraethyl orthosilicate, tetra(2-ethylhexyl) silicate and isopropyl silicate, or a combination of at least two of them.
[0021] In this embodiment, specifically, the mass ratio of the silane coupling agent and silicate hydrolysis condensation reaction is 9:1-6:4, the mass ratio of alcohol and water is 9:1-7:3, and the mass ratio of the mixture of silane coupling agent and silicate to the alcohol-water mixed solvent is 1:200-500.
[0022] In this embodiment, specifically, the catalyst added in the hydrolysis condensation is any one of ammonia water, formic acid, acetic acid, hydrochloric acid and ammonium chloride, and the mass ratio of the catalyst to the mixture of the silane coupling agent and the silicate is 1:1-10.
[0023] In this embodiment, specifically, the preparation method of the siloxane condensate is to stir at room temperature for 2 to 24 hours after hydrolysis and condensation, and then rotary evaporate to obtain the desired product; wherein the stirring speed is 200 to 500 rpm; the stirring time is 2 to 24 hours; and the rotary evaporate temperature is 80 to 110°C.
[0024] like Figure 2 As shown in the Raman spectrum of siloxane condensates, taking KH570 and tetraethyl orthosilicate as examples, 1637cm-1 represents double bonds and 484cm-1 represents silicon-oxygen bonds. The results show that the siloxane condensates still retain the functional bonds and silicon-oxygen bonds as silane coupling agents.
[0025] In this embodiment, specifically, the modified POE particles of the POE layer are prepared according to the following ratio: 100 parts of POE particles; 0.01-0.2 parts of nano-silicon dioxide; 0.2-1 parts of cross-linking agent; 0.1-0.3 parts of auxiliary cross-linking agent; 0.05-0.5 parts of light stabilizer; 0.05-0.5 parts of antioxidant; 0.5-2 parts of siloxane condensate.
[0026] In this embodiment, specifically, the particle size of the nano-silicon dioxide is 1 to 10 nm.
[0027] like Figure 3 As shown, TEM images of nano-silica and nano-silica mixture, the left image is nano-silica, and the right image is a mixture of nano-silica / additive / siloxane condensate. The results show that the additive and siloxane condensate can be well adsorbed on and around the nano-silica.
[0028] In the present embodiment, specifically, the surface of the nano-silica used contains hydroxyl groups, and the siloxane condensate is an amorphous condensate similar to a network structure. During the mixing process with the nano-silica and the additives, the hydroxyl groups on the siloxane condensate can form hydrogen bonds with the hydroxyl groups on the nano-silica, and the silicon-oxygen bonds can react and condense with the hydroxyl groups. In this process, the siloxane condensate can use its own viscosity and network structure to better wrap the additives between the nano-silica surface and the siloxane condensate. Such a reaction can more effectively limit the migration of the additives and allow the additives to better participate in the reaction in the POE layer.
[0029] In this embodiment, specifically, the raw material ratio of the EVA layer is: 100 parts of EVA particles; 0.2-1 parts of cross-linking agent; 0.1-0.3 parts of auxiliary cross-linking agent; 0.05-0.5 parts of light stabilizer; 0.05-0.5 parts of antioxidant; and 0.5-2 parts of silane coupling agent.
[0030] In this embodiment, specifically, the types of the cross-linking agent, auxiliary cross-linking agent, light stabilizer, antioxidant and silane coupling agent used in the EVA layer are the same as those used in the POE layer.
[0031] In this embodiment, specifically, the cross-linking agent is any one of dibenzoyl peroxide, diisopropylbenzene peroxide, tert-butyl peroxide 2-ethylhexyl carbonate, 1,1-di-tert-butyl peroxide cyclohexane, tert-amyl peroxide 2-ethylhexyl carbonate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di(4-methylbenzoyl) peroxide and tert-butyl peroxide-3,5,5-trimethylhexanoate.
[0032] In this embodiment, specifically, the auxiliary cross-linking agent is any one of ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane triacrylate, triallyl isocyanurate, and triallyl cyanurate.
[0033] In this embodiment, specifically, the light stabilizer is any one of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer, and a hydroperoxide decomposer light stabilizer.
[0034] In this embodiment, specifically, the antioxidant is any one of a hindered phenol antioxidant, an aromatic amine antioxidant, a phosphite antioxidant, a thioether antioxidant, and a metal passivator antioxidant.
[0035] In this embodiment, specifically, the mixing method in the preparation process of the modified POE particles is stirring or ball milling; the temperature of the melt co-extrusion is 70-100°C.
[0036] In this embodiment, specifically, the thickness of the EVA layer is 50-150 μm; the thickness of the POE layer is 150-350 μm.
[0037] like Figure 4 As shown in the SEM images of the layer made of pure POE particles and the layer made of modified POE particles, it can be seen from the comparison that the nano-silica does not agglomerate and can be well dispersed in the POE matrix.
[0038] In this embodiment, specifically, due to the large difference in polarity between POE and EVA, the polarity of POE is much lower than that of EVA, and most of the additives used in the preparation of the film have relatively high polarity. Therefore, in the preparation of the EPE film, the phenomenon of the additives migrating from the POE layer to the EVA layer often occurs, thereby affecting the performance of the EPE film. Among them, the silane coupling agent and the auxiliary cross-linking agent are the most likely to migrate. (1) The present invention adopts the method of hydrolysis and condensation of silane coupling agent and silicate, which can form an amorphous, highly viscous siloxane condensate. This substance can retain the silicon oxygen bond and functional group, so that it can also play the role of a silane coupling agent, and the high viscosity and large molecular weight make it difficult to move and more easily attached to the surface of the particles. (2) The present invention adds a certain amount of nano-silicon dioxide to the POE layer. The surface of the silicon dioxide has certain polar groups, which are more likely to combine with the polar additives, play the role of fixing the additives, and make the migration of the additives more difficult. (3) Through the combined action of highly viscous siloxane condensates and nano-silica, the migration of additives in the EPE film can be greatly reduced, thereby improving the quality and performance of the EPE film.
[0039] On the other hand, the present invention also provides a low-precipitation EPE packaging film obtained by the preparation method as described above, comprising a siloxane condensate and nano-silicon dioxide.
[0040] Example
[0041] Initial cross-linking test:
[0042] Sample preparation: After stacking two pieces of adhesive film, take a piece of adhesive film with a size of 50mm×50mm, and stack the front plate material, non-stick film, adhesive film, non-stick mold, and back plate material from bottom to top. Put the front plate downward into the vacuum laminator, and laminate according to the temperature and time required by the product, and then take it out and cool it to room temperature for use. After lamination, weigh 0.5g±0.01g and cut it into small particles with a size less than 3mm×3mm. Prepare 3 samples for each group.
[0043] Test method: 1) Wash, dry and weigh the stainless steel mesh bag as W1 (accurate to 0.001g). 2) Put the prepared sample into the stainless steel mesh bag to make a sample package, weigh it as W2 (accurate to 0.001g) 3) Seal the sample package with wire, mark it, insert it from the side of the three-necked flask and seal it with a rubber stopper, add 1 / 2 volume of xylene solvent to the flask, immerse the sample package in the solvent, put a reflux condenser in the middle of the flask, heat it to about 140℃, boil and reflux xylene for 5h, and keep the reflux rate at 20 drops / min to 40 drops / min. 4) After the reflux is completed, take out the sample package and hang it to remove the solvent droplets. 5) Put it in a vacuum oven, control the temperature at 140℃, dry it for 3h, and completely remove the solvent. 6) Take the sample package out of the oven, remove the iron wire, place it in a desiccator to cool for 30 minutes, then take it out and weigh it, recording it as W3 (accurate to 0.001g).
[0044] Result calculation: Calculate the degree of crosslinking according to the following formula, retain two decimal places after the decimal point, and take the average value of the test results.
[0045] D=[(W3-W1) / (W2-W1)]×100%
[0046] Where: D—crosslinking degree, %; W1—mass of empty stainless steel wire mesh bag, g; W2—mass of bag containing sample, g; W3—mass of sample package after solvent extraction and drying, g.
[0047] Crosslinking degree test after heating:
[0048] Add a step of heating the POE sample in an oven at 60°C for 24 hours, and the rest is the same as above.
[0049] Peel force test:
[0050] Sample preparation: 1) Prepare two pieces of adhesive film raw materials, one piece of glass and one piece of flexible backboard, all of which are 300mm×150mm in size; 2) Stack glass / adhesive film (two pieces) / flexible backboard in sequence, put them into a vacuum laminator, and laminate them according to the temperature and time required by the product. There should be no bubbles in the adhesive film in the laminated sample. Prepare 3 samples; 3) Cut the flexible backboard / adhesive film layer into samples with a width of 10mm±0.5mm every 5mm in the width direction for the peeling force test between the adhesive film and the glass.
[0051] Test process: According to the test method of GB / T2790-1995, the peeling force F between the glass and the film is measured on a tensile testing machine at a tensile speed of 100mm / min±10mm / min.
[0052] Test results: The peel strength is calculated according to the following formula, and the arithmetic mean of 3 samples is taken, accurate to 0.1N / cm.
[0053] σ=F / B
[0054] Where: σ—180° peel strength, N / cm; F—peel force, N; B—sample width, cm.
[0055] The transmittance of visible light was tested using an ultraviolet spectrophotometer (UV-6000) with a test band of 380-1100 nm; the tensile properties were tested according to GB / T1040.3-2006 with a tensile rate of 500 mm / min.
[0056] Example 1
[0057] In the first step, 9 g KH570 and 1 g tetraethyl orthosilicate were added to a mixed solution of 450 g ethanol and 50 g water, and 10 g ammonia water was added, and the mixture was reacted at 200 rpm for 24 h, and then rotary evaporated at 80° C. to obtain a siloxane condensate.
[0058] In the second step, the modified POE particles are prepared according to the following ratio:
[0059]
[0060] The obtained siloxane condensate, nano-silica, antioxidant, light stabilizer, cross-linking agent and auxiliary cross-linking agent are first mixed uniformly by stirring, then mixed with POE particles, and finally the product modified POE particles are obtained by melting, extruding and granulating.
[0061] The third step is to prepare EPE film by three-layer co-extrusion, and the EVA layer is carried out in the following proportions.
[0062]
[0063] The processing temperature is 100°C, the thickness of the EVA layer on both sides is 50μm, and the thickness of the middle modified POE layer is 350μm.
[0064] Example 2
[0065] In the first step, 7 g KH550 and 3 g tetra(2-ethylhexyl) silicate were added to a mixed solution of 120 g ethanol and 80 g water, and 1 g acetic acid was added. The mixture was reacted at 500 rpm for 2 h, and then rotary evaporated at 110° C. to obtain a siloxane condensate.
[0066] In the second step, the modified POE particles are prepared according to the following ratio:
[0067]
[0068] The obtained siloxane condensate, nano-silica, antioxidant, light stabilizer, cross-linking agent and auxiliary cross-linking agent are first mixed uniformly by stirring, then mixed with POE particles, and finally the product modified POE particles are obtained by melting, extruding and granulating.
[0069] The third step is to prepare EPE film by three-layer co-extrusion, and the EVA layer is carried out in the following proportions.
[0070]
[0071]
[0072] The processing temperature is 70°C, the thickness of the EVA layer on both sides is 50μm, and the thickness of the middle modified POE layer is 350μm.
[0073] Example 3
[0074] In the first step, 8 g KBM403, 1 g tetraethyl orthosilicate and 1 g isopropyl silicate were added to a mixed solution of 400 g isopropanol and 100 g water, and 2 g hydrochloric acid was added. The mixture was reacted at 300 rpm for 12 h, and then rotary evaporated at 90 °C to obtain a siloxane condensate.
[0075] In the second step, the modified POE particles are prepared according to the following ratio:
[0076]
[0077] The obtained siloxane condensate, nano-silica, antioxidant, light stabilizer, cross-linking agent and auxiliary cross-linking agent are first mixed uniformly by ball milling, then mixed with POE particles, and finally the product modified POE particles are obtained by melting, extruding and granulating.
[0078] The third step is to prepare EPE film by three-layer co-extrusion, and the EVA layer is carried out in the following proportions.
[0079]
[0080]
[0081] The processing temperature is 90°C, the thickness of the EVA layers on both sides is 150 μm, and the thickness of the middle modified POE layer is 150 μm.
[0082] Example 4
[0083] In the first step, 5 g KH570, 4 g KBM403 and 1 g isopropyl silicate were added to a mixed solution of 400 g ethanol and 100 g water, and 2 g hydrochloric acid was added. The mixture was reacted at 200 rpm for 16 h, and then rotary evaporated at 100 °C to obtain a siloxane condensate.
[0084] In the second step, the modified POE particles are prepared according to the following ratio:
[0085]
[0086] The obtained siloxane condensate, nano-silica, antioxidant, light stabilizer, cross-linking agent and auxiliary cross-linking agent are first mixed uniformly by stirring, then mixed with POE particles, and finally the product modified POE particles are obtained by melting, extruding and granulating.
[0087] The third step is to prepare EPE film by three-layer co-extrusion, and the EVA layer is carried out in the following proportions.
[0088]
[0089]
[0090] The processing temperature is 90°C, the thickness of the EVA layers on both sides is 100 μm, and the thickness of the middle modified POE layer is 250 μm.
[0091] Example 5
[0092] In the first step, 5g OFS-6341, 2g KH570, 2g tetraethyl orthosilicate and 1g tetra(2-ethylhexyl) silicate were added to a mixed solution of 120g ethanol and 80g water, and 1g ammonium chloride was added. The mixture was reacted at 500rpm for 2h, and then rotary evaporated at 100°C to obtain a siloxane condensate.
[0093] In the second step, the modified POE particles are prepared according to the following ratio:
[0094]
[0095] The obtained siloxane condensate, nano-silica, antioxidant, light stabilizer, cross-linking agent and auxiliary cross-linking agent are first mixed uniformly by ball milling, then mixed with POE particles, and finally the product modified POE particles are obtained by melting, extruding and granulating.
[0096] The third step is to prepare EPE film by three-layer co-extrusion, and the EVA layer is carried out in the following proportions.
[0097]
[0098]
[0099] The processing temperature is 90°C, the thickness of the EVA layers on both sides is 125 μm, and the thickness of the middle modified POE layer is 200 μm.
[0100] Comparative Example 1
[0101] The same formulation and process as the EVA layer in Example 1 are used.
[0102]
[0103] The processing temperature is 100℃ and the total thickness is 450μm.
[0104] Comparative Example 2
[0105] Using a formula and process similar to that of the POE layer in Example 1, nano-silicon dioxide and siloxane condensate were removed.
[0106]
[0107]
[0108] The processing temperature is 100℃ and the total thickness is 450μm.
[0109] Comparative Example 3
[0110] The EPE film was prepared by three-layer co-extrusion using a formula and process similar to that in Example 1, removing the nano-silicon dioxide and siloxane condensate.
[0111] The POE layer formula is as follows:
[0112]
[0113] The EVA layer formula is as follows:
[0114]
[0115] The processing temperature is 100°C, the thickness of the EVA layers on both sides is 50μm, and the thickness of the middle POE layer is 350μm.
[0116]
[0117]
[0118] The experimental results of the initial and heated crosslinking degree of Example 1 and Comparative Examples 2 and 3 show that the addition of nano-silicon dioxide and siloxane condensate can significantly improve the phenomenon of additive migration, thereby increasing the crosslinking degree of the film. From the results of the light transmittance, it can be seen that the addition amount of nano-silicon dioxide of the present invention will not reduce the light transmittance of the film.
[0119] In summary, the low precipitation EPE encapsulation film and the preparation method thereof of the present invention adopt the method of hydrolysis and condensation of silane coupling agent and silicate to form an amorphous and highly viscous siloxane condensate. The obtained siloxane condensate retains the silicon-oxygen bond and functional group to maintain the original function of the silane coupling agent, and at the same time, the high viscosity and large molecular weight make it difficult to move and easier to adhere to the surface of particles; the surface of nano-silica has certain polar groups, which is easier to combine with polar additives to play the role of fixing the additives. Through the joint action of the siloxane condensate and the nano-silica, the migration and precipitation amount of the additives in the EPE film is greatly reduced, and the quality and performance of the EPE film are effectively improved.
[0120] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a low-precipitation EPE packaging film, characterized in that: include: The raw materials of each layer are mixed and configured according to the formula, and a three-layer structure is formed by melt co-extrusion; The three-layer structure comprises a POE layer on the inner layer and an EVA layer on the outer layer; in The raw material of the POE layer is modified POE particles; The preparation method of the modified POE particles comprises the following steps: The nano-silicon dioxide, antioxidant, light stabilizer, cross-linking agent, auxiliary cross-linking agent and siloxane condensate are first mixed evenly, then mixed with POE particles, and then melted, extruded and granulated to obtain modified POE particles for standby use; The preparation method of the siloxane condensate comprises the following steps: A catalyst is added to a mixed solution of alcohol and water to hydrolyze and condense a silane coupling agent and a silicate, and a siloxane condensate is prepared by rotary evaporation; The raw materials selected for the EVA layer include EVA particles, antioxidants, light stabilizers, crosslinking agents, auxiliary crosslinking agents and silane coupling agents; The mass ratio of the silane coupling agent and the silicate hydrolysis condensation reaction is 9:1 to 6:4; The catalyst added in the hydrolysis condensation is any one of ammonia water, formic acid, acetic acid, hydrochloric acid and ammonium chloride; The modified POE particles of the POE layer are prepared according to the following ratio:
2. The preparation method according to claim 1, characterized in that The silane coupling agent is any one of KH550, KH560, KH570, KH792, OFS-6341, KBM403, KBM4803, KM5803 and DL602, or a combination of at least two thereof.
3. The preparation method according to claim 1, characterized in that: The silicate is any one of tetraethyl orthosilicate, tetra(2-ethylhexyl) silicate and isopropyl silicate, or a combination of at least two of them.
4. The preparation method according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 1 to 10 nm.
5. The preparation method according to claim 1, characterized in that: The raw material ratio of the EVA layer is:
6. The preparation method according to claim 1, characterized in that: The temperature of the melt coextrusion is 70-100°C.
7. A low-precipitation EPE packaging film obtained by the preparation method according to any one of claims 1 to 6, characterized in that: Including siloxane condensate and nano silicon dioxide.
Citation Information
Patent Citations
Polyvinyl alcohol membrane preparation method for retarding micro-molecule precipitation based on nano silica sol
CN109096665A
Composite packaging adhesive film for solar packaging material and preparation method of composite packaging adhesive film
CN109294455A
Precipitation-resistant, scratch-resistant, high-performance and low-cost polypropylene composite material and preparation method thereof
CN111087695A